Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Produk Thrifting di Pasar Mardika Kota Ambon - Agnes A Tahya; Harold Hursepuny; Evandro Manuputty; Anthoneta T Waelauruw; Eline O Hutubessy (Jurnal Administrasi Terapan, 2024)
The purpose to be achieved in this study is to find out the influence of product quality and price on the buying interest of thrifting products at Mardika Market, Ambon City. The type of research used in this study uses a quantitative analysis method. This study uses regression analysis techniques. From the results of the research that has been carried out, it is found that the quality of the product has a positive and significant effect on the buying interest of thrifting clothing consumers at the Mardika Market, Ambon City. Based on the results of the t-test, a tcount value of 8,963 > table 2,010 with a Sig. level of 0.000 < 0.025. 2. Price has a positive and significant effect on the Buying Interest of thrifting clothing consumers at Mardika Market, Ambon City. Product quality and price together have a significant effect on the buying interest of consumers of thrifting clothing at Mardika Market, Ambon City. Based on the results of the simultaneous test F, the value of Fcal was 103,746> 3.20 Ftabel and the Sig value was 0.000 < 0.05. Keywords: Product Quality; Price; Buying Interest; Thrifting Products.